Risk Factor Analysis of Type 2 Diabetes among Adolescents at Wongsonegoro Regional Hospital 2023 - Areta Maharani Putri Prihananto (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes Mellitus (DM) is a chronic condition caused by insufficient insulin production or ineffective insulin utilization by the body. In type 2 diabetes, blood sugar levels increase due to suboptimal insulin production or absorption. This study aims to identify the risk factors for Type 2 Diabetes Mellitus (T2DM) in adolescents at K.R.M.T Wongsonegoro Regional Hospital, Semarang, in 2022. This study employs an analytical observational research design with a cross-sectional approach. Data collection was conducted from May to July 2023 at the same hospital. Bivariate analysis revealed that maternal age (p=0.002) and the number of children in the family (p=0.003) had significant associations with T2DM incidence, while birth spacing (p=0.168), drinking water source (p=1.000), and latrine conditions (p=0.806) showed no significant relationships. Multivariate analysis indicated that the primary risk factors were maternal age (OR=4.429; 95% CI: 1.829-10.726) and the number of children in the family (OR=4.000; 95% CI: 1.665-9.610), with maternal age being the most critical risk factor. These findings highlight the importance of family factors in preventing T2DM in adolescents.